(untitled) (Research, Society and Development, 2021)
Sphenia fragilis is a bivalve mollusk belonging to the family Myidae, which has a habit of digging and living housed in free spaces, cavities and/or cracks left by other organisms (e.g., mussels and oysters). The species shows high morphological variation in the shape of the shell, however, this variation has not yet been studied based on morphometric data. The objective was to test the hypothesis of the existence of a stabilization of the shell shape of S. fragilis, through morphometric analysis of individuals collected on the Amazon coast. The external morphometric measurements of the shell were measured in 309 specimens, performing the morphometric characterization by means of linear regressions and the determination of the Shell Shape Stabilization Indicator (IEF). The results indicate that the species has a high morphometric correlation, however the IEF describes a high variability throughout its development. Such results refute the hypothesis of the existence of stabilization in the shape of the S. fragilis shell and, as a result, methodological adjustments are recommended in studies about the population dynamics of the species, mainly in the number of individuals analyzed.